Approaches to quantify value from business to society: Case studies of KPMG's true value methodology. Issue 4 (7th November 2016) - Hendriksen, Bernd; Weimer, Jeroen; McKenzie, Mark
Abstract : Purpose: This paper aims to present an approach to quantify in financial terms the value that companies create and reduce for society, based on the KPMG true value methodology. This methodology was developed to quantify the socio-economic and environmental value created and reduced by businesses in a format that can easily be understood and used by business leaders to affect key business decisions based on quantitative data. The paper looks at the business drivers for the development of the methodology and the implications and initial results for companies adopting it. Design/methodology/approach: Following a brief introduction of the methodology, and the factors leading up to its development, this paper will present three recent cases of companies that have applied the methodology, their motivation for using it and what some of the initial results have been. The authors led the development of the KPMG true value methodology and have been involved in the application of the methodology across various sectors and companies. Other consultants involved in the implementation of the methodology within the companies in the case studies (below) were also interviewed for this paper. Findings: The three cases above represent very different companies from various sectors. Although the approach and implementation of the KPMG true value methodology was similar across all three companies, the results, application of the results and subsequent benefits to the company in question were divergent. To date, only a handful of corporations have measured and publicly disclosed their societal value creation, but momentum is building, and, in this age of internalization, more and more companies will likely follow suit. Corporations that choose a methodology and apply it in a consistent fashion can only stand to benefit from the insights the experience brings. Research limitations/implications: This paper provides insight into the KPMG true value methodology and how it has been applied within several large companies from different sectors. Because of confidentiality issues, the companies have been anonymised, and some specific quantitative data have been omitted. This paper does not look in detail at how indicators are calculated, because of space limitations. Given the fact that the methodology has only relatively recently been introduced, long-term results are not yet available. As the methodology further develops over time, there will be considerable opportunities for academic research around the methodology, for example, looking at how the creation of value for society relates to shareholder value or environmental, social and governance performance over time. Practical implications: This paper provides examples of how companies have integrated socio-economic and non-financial metrics with standard financial metrics and some of the implications this can have on corporate decision-making processes. Originality/value: The KPMG true value methodology was introduced in 2014 with the publication of the 2014 KPMG report "A New Vision of Value: Connecting corporate and societal value creation" (available on-line). This paper is one of the first publications in an academic journal on this topic. In writing this paper, the authors do not assume that readers have previous knowledge of the methodology, and, as such, have borrowed extensively from "A New Vision of Value" in explaining the methodology. This paper, however, goes on to highlight and reflect on the experiences of some of the first companies from different sectors to use the methodology since its launch more than two years prior.